Pre-clinical assessment of SAR442257, a CD38/CD3xCD28 trispecific T cell engager in treatment of relapsed/refractory multiple myeloma - Grab, Anna Luise; Kim, Peter S.; John, Lukas; Bisht, Kamlesh; Wang, Hongfang; Baumann, Anja; Van de Velde, Helgi; Sarkar, Irene; Shome, Debarati; Reichert, Philipp; Manta, Calin-Petru; Gryzik, Stefanie; et al. (Cells, 2024)
Current treatment strategies for multiple myeloma (MM) are highly effective, but most patients develop relapsed/refractory disease (RRMM). The anti-CD38/CD3xCD28 trispecific antibody SAR442257 targets CD38 and CD28 on MM cells and co-stimulates CD3 and CD28 on T cells (TCs). We evaluated different key aspects such as MM cells and T cells avidity interaction, tumor killing, and biomarkers for drug potency in three distinct cohorts of RRMM patients. We found that a significantly higher proportion of RRMM patients (86%) exhibited aberrant co-expression of CD28 compared to newly diagnosed MM (NDMM) patients (19%). Furthermore, SAR442257 mediated significantly higher TC activation, resulting in enhanced MM killing compared to bispecific functional knockout controls for all relapse cohorts (Pearson's r = 0.7). Finally, patients refractory to anti-CD38 therapy had higher levels of TGF-β (up to 20-fold) compared to other cohorts. This can limit the activity of SAR442257. Vactoserib, a TGF-β inhibitor, was able to mitigate this effect and restore sensitivity to SAR442257 in these experiments. In conclusion, SAR442257 has high potential for enhancing TC cytotoxicity by co-targeting CD38 and CD28 on MM and CD3/CD28 on T cells.
Gesehen am 12.06.2025